CONSTRUCTION OF MDS EUCLIDEAN SELF-DUAL CODE FROM DUADIC CODE - IRAWAN (NIM : 10109109), TOMMI
The main coding theory problem is how about efficiency of the code and errorcorrecting capability of the code if it is used in communication process. Efficiency of the code is measured from size of the code and error-correcting capability is measured from minimum distance of the code. The code is called optimal if it has the highest possible minimum distance.....